Temperature sensing type wire and cable - LU FEI (2018)
The utility model belongs to the technical field of wire and cable, more specifically relates to a temperature sensing type wire and cable. Temperature sensing type wire and cable, it includes four cables, filling layer, iron shielded layer, buffer layer, temperature sensing layer and transparent protection layer, the cable includes the electrically conductive heart yearn of three mutual transposition from inside to outside in proper order, and electrically conductive heart yearn peripheral hardware has non -woven fabrics layer and insulating layer, cable sets is in iron shielded layer, the filling layer is filled in the gap between the cable, iron shielded layer has set gradually buffer layer, temperature sensing layer and transparent protection layer outward. 本实用新型属于电线电缆技术领域，更具体地，涉及种感温型电线电缆。感温型电线电缆，它包括四根电缆、填充层、金属屏蔽层、缓冲层、感温层和透明保护层，所述电缆从内到外依次包括三根相互绞合的导电芯线，导电芯线外设有无纺布层和绝缘层；所述电缆设置在金属屏蔽层内，所述填充层填充在电缆之间的缝隙内，所述金属屏蔽层外依次设置有缓冲层、感温层和透明保护层。